Developpement de la production laitiere. Compte-rendu d'un atelier - International Livestock Centre for Africa (1981)
A study on smallholder dairy development in the East African highlands. Looks into the production systems and development constraints and priorities. Discusses genetic factors, nutrition, disease, management, labour, marketing and pricing policies. Summarises research and development experiences.